2022
DOI: 10.3390/poultry1010003
|View full text |Cite
|
Sign up to set email alerts
|

Nutrigenomics in Animal Feeding: Digital Gene Expression Analysis in Poultry Fed Tenebrio molitor Larvae Meal

Abstract: The purpose of this study was to investigate the effects of high levels of Tenebrio molitor dietary inclusion (15%) on molecular mechanisms that influence poultry health in a broiler chicken diet. The global gene expression of four tissues (breast, liver, jejunum, and caecum) was evaluated using the RNA-Seq approach. The analysis of differentially expressed genes suggested that the use of Tenebrio molitor leads to the overexpression of genes related to protein elongation required for tissue growth and developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
(99 reference statements)
0
1
0
Order By: Relevance
“…This transcriptomic approach can accurately study tissue transcriptomes with high resolution and depth. Increasingly, the nutrigenomic approach is used to investigate the effect of diets on metabolic processes also in poultry (Soglia et al, 2022). A recent study of the liver transcriptome after folic acid supplementation in the diet of broiler chickens found that peroxisome proliferator activated receptor (PPAR) signalling is the pathway most activated by the enriched diet (Zhang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…This transcriptomic approach can accurately study tissue transcriptomes with high resolution and depth. Increasingly, the nutrigenomic approach is used to investigate the effect of diets on metabolic processes also in poultry (Soglia et al, 2022). A recent study of the liver transcriptome after folic acid supplementation in the diet of broiler chickens found that peroxisome proliferator activated receptor (PPAR) signalling is the pathway most activated by the enriched diet (Zhang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%